Human immunodeficiency virus infection with human granulocytic ehrlichiosis complicated by symptomatic lactic acidosis. - Springer, Sandra A; Altice, Frederick L (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2003)
Lactic acidosis has been reported as a complication associated with antiretroviral therapy; in particular, usually with use of nucleoside reverse-transcriptase inhibitors. We describe a human immunodeficiency virus (HIV)-infected patient with a history of lipodystrophy who presented with hepatic insult associated with documented human granulocytic ehrlichiosis (HGE). Despite a normal serum lactate level before the onset of acute coinfection, the patient developed symptomatic hyperlactatemia while receiving appropriate treatment for HGE. To date, this is the first presentation of symptomatic hyperlactatemia in a patient with HIV infection and HGE.
Keywords: Acidosis, Lactic; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Ehrlichiosis; HIV Infections; Humans; Lactic Acid; Male; Middle Aged; Reverse Transcriptase Inhibitors